(untitled) (Indian Journal of Animal Production and Management, 2024)
The present experiment was designed to study the effect of dietary incorporation of eucalyptus leaf powder on the average weekly feed intake and egg production of commercial laying hens. A 12-week feeding experiment was conducted on 72 White Leghorn laying chickens of 28 weeks of age. Hens were randomly assigned to one of four treatment groups, each having 18 birds and three replicates of six birds. Four treatments were included as a control (T1): basal diet, (T2): Incorporation of 0.3% eucalyptus leaf powder in the basal diet containing phytase, (T3): Incorporation of 0.45% eucalyptus leaf powder in the basal diet containing phytase, (T4): incorporation of 0. 6% eucalyptus leaf powder in the basal diet containing phytase. Daily feed intake and egg production were recorded. The results revealed that Supplementing Eucalyptus (Eucalyptus Globulus) Leaf powder did not affect the cumulative performance of laying hens in terms of feed intake and egg production (P>0.05). Based on the above findings, it was determined that adding 0.3 percent eucalyptus leaf powder to the basal diet containing phytase improves egg production. Furthermore, because Eucalyptus leaves can be procured at no cost, their incorporation is cost-effective and can help reduce feed expenditures.